The Involvement of State Gov- ernment, Agencies and Local Authority Policies on the Conser- vation of Heritage Spots in Malaysia - MOHD HIRIY GHAZALI; MOHD JANI; ABDULLAH SUMRAHADI; BAHTIAR MOHAMAD (Universitas Muhammadiyah Yogyakarta, 2017)
This paper is analyzes the local policy implementation by the state authorities at two historical cities, namely Melaka (Malacca) and George Town, Penang. Both cities are awarded as the United Nations Educational, Scientific and Cultural Or- ganization (UNESCO) World Heritage Sites. One of the most prominent compo- nent of tangible cultural heritage is historic buildings. Thus, it is essential to ensure the sustainability of those buildings so that they will keep attracting more domestic and international travelers. Lack of awareness from the local residents is one main issue arises due to some policies imposed by the local government concerning the historic buildings. This paper is based on previous literature and from findings of a study. The findings were obtained from content analysis of local daily bilingual print newspapers namely The Star and Berita Harian (BH) on the portrayal of cultural heritage in Malaysia. The result of this paper would sheds some light, especially on the conservation of historical buildings to both historical cities through the role of the state government and agencies in imple- menting and enforcing the formulated policies.